The Big Red Church - Pickford, Rollin:::::::::
Poster celebrating 50 Year anniversary of the First Congregational Church in Fresno's Tower District, 1949-1999. Painting was commissioned by the church. Three generations of Rollin's family attended the church in this and previous downtown Locations. The First Congregational Church was originally established in 1883.